Modified technique for the visualization of C6/C7 in lateral cervical spine radiography - Moey, Soo Foon; Hazri, Najwa Athirah; Che Mohamed, Norfariha (Mashhad University of Medical Sciences, 2020)
Introduction: In the Swimmer’s view, the C6 and C7 can be visualized as superimposed on the shoulders. This study aimed to explore the technique to demonstrate C1 to C7 in the lateral spine and improve the diagnostic value in that region. Material and Methods: An experimental study was carried out using a RANDO phantom to obtain images of the lateral cervical spine. Twelve radiographs were taken using different kVps at different centering points. The image quality of the radiographs was evaluated by two radiographers using the modified image quality criteria score sheet adapted from the Commission of European Communities on image quality. A dose area product meter was utilized to estimate the entrance surface dose (ESD); however, CALDose_X5 Monte Carlo software was used to estimate the effective dose. Results: The findings indicated that a higher centering point at 2 inches above the pinna of the ear can clearly visualize the lower cervical spine (C6/C7) and cervicothoracic junction (C7/T1). The results of the Kruskal-Wallis test revealed significant differences (p<0.05) in the image quality at different centering points. However, no significant differences were observed (p>0.05) in the ESD between different utilized centering points. The effective dose of the modified technique was reported to be lower, compared to that for the Swimmer’s view. Conclusion: The modified lateral technique can be used to replace the Swimmer’s view to adequately demonstrate the lower cervical spine and cervicothoracic junction with a lower radiation dose while not harming the patient due to movement during positioning